Facilitators of Elderly Care at Home and the Educational Needs of the Family Caregivers of Older Adults in the South of Tehran, Iran: A Qualitative Study - Fatemeh Rahimi; Elham Shakibazadeh; Mahnaz Ashoorkhani; Mahshid Foroughan (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Population aging is accompanied by an increase in the elderly's demand for long-term care, which is mainly provided by family caregivers. Providing quality elderly care, while maintaining the health of caregivers, requires recognition of facilitators and the educational needs. Therefore, this study aims to investigate facilitators of elderly care at home and the educational needs of the family caregivers of older adults in the south of Tehran, Iran. Methods & Materials This is a qualitative study using the conventional content analysis method. To collect data, we conducted semi-structured telephone interviews. Seventeen family caregivers aged ≥18 years with at least one month of caregiving experience and at least six hours of caregiving per week were selected using purposive and snowball sampling methods until data saturation from January to April 2021. After transcribing the recorded interviews, the data were entered into the MAXQDA 2018 software and analyzed. Results Personal factors included personal characteristics of caregivers, Capability in caregiving, perceived benefits of caregiving, and self-care activities of caregivers. Interpersonal factors included proper relationship with older adults, older adults' partial  dependence on caregivers, cooperation and support of family members, and receiving others' support. Supportive environments included physical environment, receiving support from work environments and organizations providing elderly care services. The most important educational needs of family caregivers were the needs to learn how to prepare nutritious foods for the elders, the way to nourish older adults with dysphagia, and how to move the physically disabled older adults. Conclusion Family caregivers of older adults in the south of Tehran should have access to affordable elderly care and home care services based on their educational needs that require planned support from service providers.